Carding process of polyacrylonitrile pre-oxidized fiber for carbon cloth
By using appropriate process parameters and pretreatment reagents in the cotton spinning equipment, the roll wrapping and blocking problems of polyacrylonitrile preoxidized fibers in the carding stage are solved, the production efficiency of carbon cloth electrodes is improved, and the iron-chromium liquid flow battery is promoted industrialization process.
Patent Information
- Application Number
- CN202411278727.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-01-03
AI Technical Summary
The existing cotton spinning equipment process is not suitable for polyacrylonitrile preoxidized fibers, which leads to rolling and blocking during the carding stage, affecting the production efficiency of carbon cloth electrodes and hindering the industrialization development of iron-chromium flow batteries.
Using the process principle of 'heavy pressurization, low speed, large spacing, light quantification', combined with pretreatment reagent spraying to enhance the fiber joint force, use cotton spinning equipment to card the polyacrylonitrile preoxidized fibers, adjust the cover plate and tin forest , spacing and speed of , douver rollers and douver reduces the phenomenon of wrapping rollers and breaking.
It improves the pre-spinning efficiency of polyacrylonitrile pre-oxidized fibers, reduces equipment entanglement and fluffy and decapitated tampons, improves the production efficiency of carbon cloth, and promotes the industrial development of iron-chromium flow batteries.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carding polyacrylonitrile pre-oxidized fibers, and in particular to a carding process of polyacrylonitrile pre-oxidized fibers for carbon cloth. Background Art
[0002] Liquid flow battery is a large-scale and efficient electrochemical energy storage technology. At the same time, as an electrochemical energy storage device with low cost, high flexibility, fast response, simple structure and applicable to a wide temperature range, iron-chromium liquid flow battery can effectively solve the fluctuation problem of renewable energy such as wind energy and solar energy. It is considered to be one of the preferred technologies for large-scale energy storage and has attracted much attention in recent years. Electrodes are key components of batteries. The current mainstream electrode materials are carbon-based materials, including carbon cloth. Research on carbon cloth electrodes is also a necessary choice to improve the efficiency of iron-chromium liquid flow batteries and improve electrode performance.
[0003] Regarding the preparation technology of carbon cloth electrodes, the current domestic method is to cut the polyacrylonitrile pre-oxidized fiber filaments into strips, and then spin the yarns through the ring spinning system of the cotton spinning equipment, such as carding, drawing, roving and spun yarn, and then weave them into carbon cloth fabrics. After carbonization and graphitization, the carbon cloth fabrics are used as electrodes in iron-chromium liquid flow batteries.
[0004] Cotton spinning equipment is mainly used to process natural fibers such as cotton. Cotton fibers have natural curls in the longitudinal direction, small fiber modulus, and the main component is cellulose. These characteristics allow cotton fibers to hug and rub against each other in the pre-spinning process and smoothly form strips. Cotton spinning equipment sets the process according to the characteristics of cotton fibers, including the cylinder-cover gauge, the relative speed of the cylinder-cover, the speed ratio of the cylinder-doffer, etc., focusing on combing the natural curl of cotton fibers, eliminating the front and rear hooks of cotton fibers, and forming raw strips with neatly arranged fibers.
[0005] As a new type of high-performance fire-proof and flame-retardant material that is resistant to high temperatures and does not extend flame, polyacrylonitrile pre-oxidized silk has a higher oxygen index content and fiber carbon content than cotton fiber. The fiber is brittle, hard, and has poor spinnability. In addition, the pre-oxidized silk fiber does not have natural curl, and the artificially given curl number is a fixed value, which is insufficient to provide the pre-oxidized silk fiber with sufficient cohesive force and friction in the pre-spinning stage, resulting in obvious static electricity in the opening and combing stage, inability to form strips or fluffy slivers, equipment blockage, and a high breakage rate in the spinning stage, which seriously affects efficiency.
[0006] Therefore, the combing process of cotton spinning equipment for cotton fibers is not suitable for polyacrylonitrile pre-oxidized fibers. It is urgent to develop a new combing process to solve the problems of easy entanglement and clogging of polyacrylonitrile pre-oxidized fibers for carbon cloth when using cotton spinning equipment. This is an important measure to accelerate the research progress of carbon cloth electrodes and promote the industrialization development of iron-chromium liquid flow batteries. Summary of the invention
[0007] In order to solve the problems existing in the prior art, the present invention provides a combing process of polyacrylonitrile pre-oxidized fibers for carbon cloth. The process is different from the process of combing cotton fibers in cotton spinning equipment. The polyacrylonitrile pre-oxidized fibers for carbon cloth are sequentially subjected to the steps of feeding cotton, opening, combing, and forming into strips. According to the characteristics of polyacrylonitrile pre-oxidized fibers such as brittle shadow, easy entanglement, and strong fluffiness, the process principle of "heavy pressure, low speed, large gauge, and light quantity" is adopted to solve the problems mentioned in the above background technology.
[0008] To achieve the above object, the present invention provides the following technical solution: A carding process of polyacrylonitrile pre-oxidized fiber for carbon cloth, comprising the following steps:
[0009] S1. Setting the pre-spinning process conditions;
[0010] S2, pretreatment of polyacrylonitrile preoxidation fibers;
[0011] S3. Combing the pretreated polyacrylonitrile pre-oxidized fiber using cotton spinning equipment to obtain a finished raw sliver.
[0012] Preferably, in step S1, the temperature of the pre-spinning process is controlled at 22°C to 28°C, and the relative humidity is controlled at 65% to 78%. The raw materials should not stay on the production line for too long, on the one hand to reduce the loss of fiber moisture, and on the other hand to avoid the possibility of polyacrylonitrile pre-oxidized fiber increasing the possibility of roller entanglement due to reduced humidity.
[0013] Preferably, in step S2, the pretreatment of the polyacrylonitrile preoxidized fiber refers to spraying 0.4wt%-1.5wt% of a pretreatment agent on the polyacrylonitrile preoxidized fiber to maintain the fiber health, and then sealing and standing for more than 48 hours after spraying, in order to increase the cohesion between the fibers and reduce static electricity during the production process.
[0014] Preferably, the pretreatment reagent consists of the following components in percentage by mass:
[0015] Oil: 5wt%;
[0016] Antistatic agent: 5wt%;
[0017] Purified water: 90wt%.
[0018] Preferably, the oil selected as the pretreatment agent is required to have good hygroscopicity and low adhesion to avoid the phenomenon of fibers being entangled with the cylinder and the licker-in roller during the carding stage; the oil is composed of the following components in parts by weight:
[0019] Emulsified silicone oil: 40-50 parts by weight;
[0020] Inorganic adhesive: 5-15 parts by weight;
[0021] Organic adhesive: 1-2 parts by weight;
[0022] Chlorinated polyethylene emulsion: 1-2 parts by weight;
[0023] Surfactant: 1-3 parts by weight;
[0024] Polyacrylamide: 30-52 parts by weight.
[0025] Preferably, the polyacrylonitrile pre-oxidized fiber is a 38 mm short fiber, a 51 mm medium-long fiber or a 64 mm medium-long fiber, which is suitable for polyacrylonitrile pre-oxidized fiber of common specifications in the market.
[0026] Preferably, in step S3, when the pretreated polyacrylonitrile pre-oxidized fiber is combed using cotton spinning equipment, the distance between the rotary cover plate and the cylinder is appropriately increased compared with that when spinning cotton to avoid the cylinder winding. Therefore, the five-point distances of the cover plate and the cylinder are set to 0.3mm, 0.2mm, 0.2mm, 0.2mm, and 0.3mm, the distance between the cotton feed plate and the licker-in roller is 0.3mm, the distance between the licker-in roller and the cylinder is 0.18mm, and the distance between the cylinder and the doffer is 0.13mm.
[0027] Preferably, in step S3, when the pretreated polyacrylonitrile pre-oxidized fiber is combed using cotton spinning equipment, a suitable tin-to-thorn ratio is selected to reduce the number of cotton knots in the raw sliver, and the cylinder speed is set to 275-310r / min, and the licker-in roller speed is set to 720-780r / min; reducing the raw sliver basis weight and output speed can make the fibers fully combed and reduce roller entanglement, so the raw sliver basis weight range is controlled to be 18-22g / 5m, and the doffer speed is controlled to be 20-22r / min.
[0028] Preferably, the CV value of the raw strips is 3.3-3.6%.
[0029] Preferably, due to the poor cohesion between the pre-oxidized polyacrylonitrile fibers, the pressure on the cotton feeding roller is increased by 20% compared with that during cotton spinning to enhance the holding force during cotton feeding.
[0030] The beneficial effects of the present invention are:
[0031] 1) The present invention is a carding process for polyacrylonitrile preoxidized fiber for carbon cloth, which is different from the carding process for cotton fiber and ordinary chemical fiber, and proposes a cover plate-cylinder, licker-in-cylinder-doffer spacing, licker-in-cylinder-doffer speed suitable for polyacrylonitrile preoxidized fiber, and a pretreatment method suitable for polyacrylonitrile preoxidized fiber. It solves the problems of polyacrylonitrile fiber entanglement and clogging in cotton spinning carding machines, and fluffy and easy-to-break cotton strips, can improve the pre-spinning efficiency of polyacrylonitrile preoxidized fiber, and promote the industrialization development of iron-chromium liquid flow batteries.
[0032] 2) The process of the present invention improves the efficiency of polyacrylonitrile pre-oxidized fibers in the combing stage of cotton spinning equipment, improves the cohesion and friction between fibers, reduces equipment entanglement and the phenomenon of fluffy and broken cotton strips, effectively improves the efficiency of carbon cloth front-end production, and promotes the industrialization of iron-chromium liquid flow battery carbon cloth production. The pretreatment reagent for polyacrylonitrile pre-oxidized fibers for carbon cloth of the present invention is suitable for polyacrylonitrile short fibers of common specifications in the market. The fiber cohesion after health treatment is enhanced, the sliver dryness value is reduced, and the uniformity is improved. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] The production temperature is maintained at about 28°C and the humidity is about 70%. Polyacrylonitrile pre-oxidized fiber, with a specification of 1.44dtex*38mm and a quantity of 100KG, is put into the spinning production line. The pretreatment reagent configuration ratio is 0.025kg oil agent, 0.025kg antistatic agent, and 0.45kg water, which are evenly sprayed on the fiber and sealed and left to stand for 48 hours. The oil agent contains 45% emulsified silicone oil, 5% inorganic adhesive, 1% organic adhesive, 2% chlorinated polyethylene emulsion, 3% surfactant, and 44% polyacrylamide. The above components are all conventional commercial products, so there is no special limitation.
[0036] When the polyacrylonitrile pre-oxidized fiber is carded using a cotton spinning device, the cylinder speed is set to 270r / min, the licker-in speed is 720r / min, the raw sliver weight range is 18-22g / 5m, the doffer speed is 20r / min, the cotton feed plate-licker-in gauge is 0.3mm, the licker-in gauge is 0.18mm, the cylinder-doffer gauge is 0.13mm, and the cylinder-cover five-point gauges are 0.3mm, 0.2mm, 0.2mm, 0.2mm, 0.3mm. The raw sliver has a CV value of 3.6%.
[0037] Example 2
[0038] Keep the production temperature at about 28℃ and the humidity at about 70%. Polyacrylonitrile pre-oxidized fiber, specification 1.44dtex*51mm, quantity 200KG, put into the spinning production line. The pretreatment reagent configuration ratio is 0.04kg oil agent, 0.04kg antistatic agent, 0.72kg water, spray evenly on the fiber, seal and stand for 48 hours. The oil agent contains 50% emulsified silicone oil, 5% inorganic adhesive, 2% organic adhesive, 1% chlorinated polyethylene emulsion, 2% surfactant, and 40% polyacrylamide.
[0039] When the polyacrylonitrile pre-oxidized fiber is carded using a cotton spinning device, the cylinder speed is set to 285r / min, the licker-in speed is 780r / min, the raw sliver weight range is 18-22g / 5m, the doffer speed is 22r / min, the cotton feed plate-licker-in gauge is 0.3mm, the licker-in gauge is 0.18mm, the cylinder-doffer gauge is 0.13mm, and the cover plate five-point gauges are 0.3mm, 0.2mm, 0.2mm, 0.2mm, 0.3mm. The raw sliver has a CV value of 3.3%.
[0040] Comparative Example 1
[0041] Keep the production temperature at about 28℃ and the humidity at about 70%. Polyacrylonitrile pre-oxidized fiber, specification 1.44dtex*38mm, quantity 100KG, put into the spinning production line. The pretreatment reagent configuration ratio is 0.025kg oil agent, 0.025kg antistatic agent, 0.45kg water, spray evenly on the fiber, seal and stand for 48 hours. The oil agent contains 45% emulsified silicone oil, 5% inorganic adhesive, 1% organic adhesive, 2% chlorinated polyethylene emulsion, 3% surfactant, and 44% polyacrylamide.
[0042] The cotton fiber combing parameters used are: cylinder speed 330r / min, licker-in roller speed 800r / min, doffer speed 20r / min, feed plate and licker-in roller gauge 0.23mm, licker-in roller and cylinder gauge 0.15mm, cylinder doffer gauge 0.13mm, cylinder-cover plate five-point gauge 0.23mm, 0.20mm, 0.20mm, 0.20mm, 0.23mm.
[0043] The CV value of the raw sliver is 4.7%, and the cotton neps in the cotton web are obvious, with a lot of falling lint. Through the analysis of the fiber state in the raw sliver, the fast licker-in-cylinder speed during the carding process causes the fibers to hang on each other and form knots, and the sliver is difficult to form, and the carding machine breaks the sliver frequently. Therefore, it can be seen that the conventional cotton fiber carding parameter process is not suitable for polyacrylonitrile pre-oxidized fibers.
[0044] Comparative Example 2
[0045] Keep the production temperature at about 28℃ and the humidity at about 70%. Polyacrylonitrile pre-oxidized fiber, specification 1.44dtex*51mm, quantity 30KG, put into the spinning production line. The pretreatment reagent configuration ratio is 0.0075kg antistatic agent, 0.1425kg water, no oil agent, evenly spray on the fiber, seal and stand for 48 hours.
[0046] The cylinder speed is 285r / min, the licker-in speed is 780r / min, the doffer speed is 22r / min, the feed plate-licker-in gauge is 0.3mm, the licker-in gauge is 0.18mm, the cylinder-doffer gauge is 0.13mm, and the five-point gauges of the cover are 0.3mm, 0.2mm, 0.2mm, 0.2mm, and 0.3mm.
[0047] The CV value of the obtained carded sliver was 4.0%. No oil was used in the pretreatment reagents, the equipment frequently gave alarms during the carding process, and the blockage and roller winding phenomena were serious, and no carded sliver was formed for complete production in the subsequent process.
[0048] According to the production conditions of the above embodiments and comparative examples, the process of using cotton spinning equipment to comb polyacrylonitrile pre-oxidized fibers for carbon cloth proposed in the present invention is suitable for fibers of common specifications in the market, and in the embodiment, the production index of 51mm fibers is better than that of 38mm fibers; the slivers are formed smoothly during the combing process, and the equipment roller winding, blockage, and electrostatic adsorption phenomena are greatly reduced. At the same time, the CV value of the raw sliver is in line with the market average level and meets the requirements of the subsequent processes.
[0049] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0050] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A carding process for polyacrylonitrile pre-oxidized fiber for carbon cloth, characterized in that: The steps include: S1. Setting the pre-spinning process conditions; S2, pretreatment of polyacrylonitrile preoxidation fibers; S3. Combing the pretreated polyacrylonitrile pre-oxidized fiber using cotton spinning equipment to obtain a finished raw sliver.
2. The carding process of polyacrylonitrile pre-oxidized fiber for carbon cloth according to claim 1, characterized in that: In step S1, the temperature of the pre-spinning process is controlled at 22° C. to 28° C., and the relative humidity is controlled at 65% to 78%.
3. The carding process of polyacrylonitrile pre-oxidized fiber for carbon cloth according to claim 1, characterized in that: In step S2, the pretreatment of the polyacrylonitrile preoxidized fiber refers to spraying 0.4wt%-1.5wt% of a pretreatment agent on the polyacrylonitrile preoxidized fiber to cure the fiber, and sealing and standing for more than 48 hours after spraying.
4. The carding process of polyacrylonitrile pre-oxidized fiber for carbon cloth according to claim 3, characterized in that: The pretreatment reagent is composed of the following components in percentage by mass: Oil: 5wt%; Antistatic agent: 5wt%; Purified water: 90wt%.
5. The carding process of polyacrylonitrile pre-oxidized fiber for carbon cloth according to claim 4, characterized in that: The oil comprises the following components in parts by weight: composition: Emulsified silicone oil: 40-50 parts by weight; Inorganic adhesive: 5-15 parts by weight; Organic adhesive: 1-2 parts by weight; Chlorinated polyethylene emulsion: 1-2 parts by weight; Surfactant: 1-3 parts by weight; Polyacrylamide: 30-52 parts by weight.
6. The carding process of polyacrylonitrile pre-oxidized fiber for carbon cloth according to claim 1, characterized in that: The polyacrylonitrile pre-oxidized fiber is a 38 mm short fiber, a 51 mm medium-long fiber or a 64 mm medium-long fiber.
7. The carding process of polyacrylonitrile pre-oxidized fiber for carbon cloth according to claim 1, characterized in that: In step S3, when the pretreated polyacrylonitrile pre-oxidized fiber is combed using a cotton spinning device, the five-point spacings of the cover plate and the cylinder are set to 0.3 mm, 0.2 mm, 0.2 mm, 0.2 mm, and 0.3 mm, the cotton feed plate-licker-in spacing is 0.3 mm, the licker-in spacing is 0.18 mm, and the cylinder-doffer spacing is 0.13 mm.
8. The carding process of polyacrylonitrile pre-oxidized fiber for carbon cloth according to claim 1, characterized in that: In step S3, when the pretreated polyacrylonitrile pre-oxidized fiber is combed using a cotton spinning device, the cylinder speed is set to 275-310 r / min, the licker-in speed is set to 720-780 r / min; the sliver weight range is controlled to be 18-22 g / 5 m, and the doffer speed is set to 20-22 r / min.
9. The carding process of polyacrylonitrile pre-oxidized fiber for carbon cloth according to claim 1, characterized in that: The CV value of the raw strips is 3.3-3.6%.
Citation Information
Patent Citations
Kapok fiber pretreatment auxiliary agent and kapok fiber pretreatment method
CN103255621A
Synthesis method for inorganic fiber softener
CN104313942A
Mineral fiber softening agent
CN105155267A
Production method of flame-retardant high-temperature resistant pre-oxidized fiber aramid fiber blended yarn
CN111270380A
Carbon fiber pretreatment liquid as well as preparation method and application thereof
CN116732777A
